Geopolitical Proselytizing in the Marketplace for Loyalties Rethinking the Global Gospel of American Christian Broadcasting - Serazio, Michael (2009)
Christian televangelists in the United States have long sought overseas audiences for their religious broadcasts, though less notice has been taken of the geopolitical implications of that engagement. Drawing upon a review of evidence from academic literature, popular reporting, the religious press, government data, and first-hand interviews, this critical essay employs Joseph's Nye's concept of "soft power" and Monroe Price's "marketplace for loyalties" to explore relevant historical and contemporary examples, contexts, conflicts, and strategies of that global gospel. I advocate for a future research agenda that pursues more fully the consequences of that engagement from both a production and reception standpoint.